Legal Consequences of Inter-Inmate Violence in Overcrowded Correctional Institutions: A Case Study of Kuningan Class IIA Prison - Sarip Hidayat; Suwari Akhmaddhian; Andri Hendriawan (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2025)
his study aims to analyse the legal consequences of violence between inmates under conditions of overcrowding at the Class IIA Kuningan Penitentiary. Overcrowding, or overcrowding exceeding the ideal capacity, is a significant factor in the increased potential for conflict and violence within the prison. The research method is a juridical-empirical approach that combines normative studies of correctional regulations with empirical analysis through interviews and field observations. The results show that violence between inmates has various legal consequences for both perpetrators and victims, including disciplinary sanctions, reduced behavioural assessments, restrictions on correctional rights, and the possibility of new criminal offences under the Criminal Code. For victims, violence requires special protection, rehabilitation, and strengthening of complaint mechanisms. Furthermore, overcrowding has been shown to worsen the effectiveness of correctional facilities and hinder the function of prisons as rehabilitative institutions. This study emphasises the need for correctional policy reform, including reducing overcrowding, increasing the number and competence of officers, and implementing a technology-based monitoring system to prevent future violence.